Earthquake Disaster Risk Analysis in South Morotai Tourism Area - Risky Nuri Amelia; Marwis Aswan (TECHNO: JURNAL PENELITIAN, 2022)
Morotai is located in the subduction zone of the Philippine Sea Plate and has the potential to be a threat to earthquake disasters. Given that the Morotai region tourism area has the potential to be threatened by earthquakes, it is necessary to prepare a Disaster Risk Assessment (KRB) in the Tourism Area, especially in South Morotai. The purpose of the disaster risk analysis study in the tourism area is to identify potential hazards based on earthquake vulnerability, and prepare a disaster risk assessment in the South Morotai priority tourism area. The risk assessment research conducted uses earthquake hazard information with the maximum ground acceleration value on the surface (PGA) obtained from updated results that have been carried out by PusGEn. The earthquake disaster risk assessment resulting from the analysis of hazard, vulnerability and capacity is obtained in the form of a high disaster risk level. Areas with high disaster risk are Daruba Village (score 11.1) and Darame Village (13.9). However, in terms of the area at high risk, Daruba Village has a large area of 15.1 km2. A planning strategy is needed for the development of disaster resilient tourism destinations by analyzing the 6A factors, namely attractions, accessibility, amenities, available packages, activities, and ancillary services.